Differential plant responses, morphometrics and electrophoretic patterns of some Meloidogyne spp. from Costa Rica and Florida U.S.A. and the description of Meloidogyne salasi sp. n - López Chaves, Róger (University of Florida, 1984)
Tesis (Doctor of Philosophy)--University of Florida, 1984